Designing a novel red to near-infrared persistent phosphor CaMgGe2O6:Mn2+, Sm3+ based on a vacuum referred binding energy diagram. Issue 29 (28th June 2019) - Ye, Qiangfei; Wang, Yuhua; Guo, Haijie; Zhou, Xufeng; Feng, Peng; Ding, Songsong
Abstract : We constructed an empirical energy level scheme of the CaMgGe2 O6 :Ln 2+ /Ln 3+ phosphors and improved the persistent luminescent properties of the sample, which the persistence duration was three times that of the red commercial phosphor Y2 O2 S:Eu 3+ . Abstract : In this work, we designed and successfully synthesized a novel germanate-based persistent luminescence (PersL) phosphor host, CaMgGe2 O6, via a solid-state reaction. We constructed an empirical energy level scheme of the CaMgGe2 O6 :Ln 2+ /Ln 3+ phosphors according to the Dorenbos model. Then, we successfully theoretically predicted the choice of the optimal codopant of CaMgGe2 O6 :Mn 2+ phosphors using this empirical energy level scheme. As a result, after co-doping with Sm 3+, the PersL intensity is increased 16 times and the time duration is effectively improved 52 times due to the high concentration of new traps. CaMgGe2 O6 :Mn 2+, Sm 3+ shows red to near-infrared long persistent emission located at 675 nm, which can be sustained for about 60 minutes above the recognizable intensity level (≥0.32 mcd m −2 ), and the persistence duration of samples was three times that of the red commercial phosphor Y2 O2 S:Eu 3+ . The experimental results coincide well with the theoretical predictions. These results demonstrate that the strategy concepts of this work are feasible for the design of persistent luminescence materials. Moreover, a possible afterglow mechanism is studied and discussed with the assistance of thermoluminescence (TL) curves.